2018
DOI: 10.1007/s10555-018-9734-0
|View full text |Cite
|
Sign up to set email alerts
|

Roles of prostaglandins in tumor-associated lymphangiogenesis with special reference to breast cancer

Abstract: Lymphangiogenesis (formation of new lymphatic vessels), unlike angiogenesis, has been a lesser-focused field in cancer biology, because of earlier controversy regarding whether lymphatic metastasis occurs via pre-existing or newly formed lymphatics. Recent evidence reveals that peri-tumoral or intra-tumoral lymphangiogenesis is a precursor for lymphatic metastasis in most carcinomas and melanomas. Two major lymphangiogenic factors, vascular endothelial growth factor (VEGF)-C and VEGF-D, are produced by cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 111 publications
1
43
0
Order By: Relevance
“…As a result, physiological or pathological processes follow [23,42]. Recent investigations support that PGE 2 may enhance progression of colorectal cancer [41,43,44], and EP4 is a therapeutic target for cancer therapy [45,46]. COX-2 derived PGE 2 can also contribute to tumor development through several mechanisms including inhibition of apoptosis.…”
Section: Pges and Their Receptorsmentioning
confidence: 99%
“…As a result, physiological or pathological processes follow [23,42]. Recent investigations support that PGE 2 may enhance progression of colorectal cancer [41,43,44], and EP4 is a therapeutic target for cancer therapy [45,46]. COX-2 derived PGE 2 can also contribute to tumor development through several mechanisms including inhibition of apoptosis.…”
Section: Pges and Their Receptorsmentioning
confidence: 99%
“…The repertoire of NRP2 ligands within the VEGF family comprises VEGF-A 145 and VEGF-C. Upon binding its ligand, NRP2 forms a ternary complex with VEGF-C and VEGFR3 on lymphatic ECs and is involved in lymphangiogenesis [61,116].…”
Section: Potential Nrp Interaction Partners: Extracellular Solublementioning
confidence: 99%
“…This pathway is thought to be involved in alterations observed in lymphedematous tissues, such as fibrosis, adipose deposition, and lymphatic dysfunction (48,90). Interestingly, it has been recently observed that cyclooxygenase (COX)2 and its product prostaglandin (PG)E2 are overexpressed in breast cancer stroma, having a possible role in lymphangiogenesis and metastatic spread s through lymphatics (91). Specifically, PGE2 activates the EP4 receptor in cancer cells and macrophages, promoting local VEGF-C/D overexpression, and LECs proliferation (91).…”
Section: Immunomodulation and Inflammatory Responsementioning
confidence: 99%
“…Interestingly, it has been recently observed that cyclooxygenase (COX)2 and its product prostaglandin (PG)E2 are overexpressed in breast cancer stroma, having a possible role in lymphangiogenesis and metastatic spread s through lymphatics (91). Specifically, PGE2 activates the EP4 receptor in cancer cells and macrophages, promoting local VEGF-C/D overexpression, and LECs proliferation (91). All this information opens new avenues in BCRL risk stratification, providing that further prospective clinical studies will be designed to investigate whether NFKB2, IL10, IL4, and EP4 can be employed as circulating biomarkers for pre-surgical risk assessment.…”
Section: Immunomodulation and Inflammatory Responsementioning
confidence: 99%